Phases of human development: Comparing Western and Islamic theories and the implication in Islamic education - Salami Mahmud; Nurul Fajri Ulfah; Syiva Fitria; Fatmawati Fadli (Atfaluna: Journal of Islamic Early Childhood Education, 2023)
The physical, cognitive, and socio-emotional development determine every aspect of human life, including education. Providing appropriate education for children is determined by the child's developmental stage. The current study aims to describe the stages of human development according to Western and Islamic concepts and their implications in Islamic education. To ensure a comprehensive investment in human beings, attention to religious education and introducing religious instruction from the prenatal stage is deemed necessary, as this period forms the foundation for further development. The research methodology employed in this study is a Systematic Literature Review (SLR). After reviewing various literature sources, the researchers selected several references that were relevant to the topic. The study's results indicate that the prenatal phase in Islamic psychology is more extended than Western psychology's. The tamyiz and amrad phases, viewed in Islamic psychology as preparations for entering adulthood, correspond to the Western psychological perspective of puberty. The futuh phase, or the phase of wisdom in Islamic psychology, occurs when a person ages 40, whereas Western psychology labels this as the adult phase. The phase of the Hereafter is considered crucial in Islamic psychology, while Western psychology lacks an afterlife phase. Consequently, Muslims undergo lifelong education from early birth to death. In conclusion, every phase of human life must be educated according to the level of maturity, starting from prenatal, infant, early childhood, school age, adolescent, young adult, mature adult, to late adult.